Analisis Pengaruh Retur Penjualan, Harga Penjualan, dan Kuantitas Penjualan terhadap Laba Penjualan Laptop pada Javara Computer Periode 2020–2025 - azizah khasanah; Suprihati; Rukmini (JURNAL ILMIAH EDUNOMIKA, 2026)
at Javara Computer during the period 2020–2025. This research employed a quantitative method using secondary data in the form of monthly sales reports from 2020 to 2025. The sample consisted of 72 observations, which were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, sales returns have a negative and significant effect on sales profit, selling prices have no significant effect on sales profit, while sales quantity has a positive and significant effect on sales profit. Simultaneously, sales returns, selling prices, and sales quantity have a significant effect on sales profit. The Adjusted R Square value of 0.953 indicates that 95.3% of the variation in sales profit can be explained by these three variables, while the remaining 4.7% is influenced by other variables outside the scope of this study. Keywords: Sales Returns, Selling Price, Sales Quantity, Sales Profit.